Problem Qiraah Muntijah Naṣr Ḥāmid Abū Zayd - Nurjiin Brury At Thoriq, Ibnu (CV Kalimasada Group, 2024)
The theme of hermeneutics in the Quran often promises a heated debate and is always interesting to observe. Although perhaps methodologically, no new issues are raised, the gap between Islam as das sollen and Muslim civilisation as das sein, especially in the modern era, remains a highlight for the academic world. Some are on the side of accommodating the times and are not reluctant to change values that are considered out of date. Naṣr Ḥāmid Abū Zayd is in that position by offering the idea of Qiraah Muntijah as a solution.